Hubungan Motivasi, Kepemimpinan, dan Budaya Organisasi Dengan Organization Citizenship Behavior (OCB) Pada Perawat Rumah Sakit Jiwa Grhasia - Devita Candrasari; Ahmad Ahid Mudayana (International Journal of Healthcare Research, 2020)
Background : Human resources are hospital assets that play a role in hospital services. One of the human resources in the hospital is a nurse. Nurses are front-line employees of the hospital who often interact with patients and play an important role in creating a good image of hospitals that often interact with patients by providing the best service. To achieve the highest quality of service, nurses must have a strong motivation, leaders who inspire subordinates, a culture of help to provide the best service. Nurses' attitudes and behavior in providing the best service aims to improve the effectiveness of hospital performance without ignoring individual productivity goals known as the Organization Citizenship Behavior (OCB). This study aims to determine the relationship of motivation, leadership, and organizational culture with Organization Citizenship Behavior toward nurses in Grhasia Psychiatric Hospital. Methods : This study was a quantitative analytic research with a cross sectional design. The research subjects were nurses of Grhasia Psychiatric Hospital involved to 66 nurses. The research instrument is a questionnaire. Data analysis with unvariate and biavariate analysis. Result: The bivariate analysis showed that there was a relationship between motivation and OCB toward nurses in Grhasia Psychiatric Hospital p-value = 0.010. There is a relationship between leadership and OCB toward nurses in Grhasia Psychiatric Hospital p-value = 0,001. There is a relationship between organizational culture and OCB toward nurses in Grhasia Psychiatric Hospital p-value = 0.031. Conclusion: There was a relatioship of motivation, leadership, and organization culture with Organization Citizenship Behavior (OCB) toward nurses in Grhasia Psychiatric Hospital.